In-situ temperature regulation of flexible supercapacitors by designing intelligent electrode with microencapsulated phase change materials. (20th February 2020) - Xu, Xiao-ying; Liu, Jia-hua; Ouyang, Xing; Cui, Lifeng; Hong, Jiaoling; Meng, Xiao; Qin, Siyin; Liu, Chen; Tang, Jiaoning; Chen, Da-Zhu
Abstract: Benefiting from the on-going update of wearable electrical devices, flexible supercapacitors have attracted extensive attention in energy storage devices. However, the challenge still exists in achieving high electrochemical performance and cycling stability at high operating temperatures. Herein, an innovative in-situ thermal management system by rationally implanting microencapsulated phase change materials (MPCMs) into three-dimensional porous reduced graphene oxide/polyaniline (GP) frameworks on the surface of carbon nanotube film (CNF) was developed for flexible all-solid-state supercapacitors via facile one-pot electrochemical co-deposition method. The flexible sandwich-shaped all-solid-state supercapacitors using hybrid CNF/GP/MPCMs as electrodes and PVA-H2 SO4 as the gel electrolyte were successfully assembled. The incorporation of MPCMs effectively suppressed the temperature fluctuation of the supercapacitor and promoted its operation stability at high temperatures. The supercapacitor containing MPCMs showed superior long-term cyclic stability in comparison with the counterpart without MPCMs. Moreover, the as-prepared supercapacitor was capable of enduring deformations of various angles and maintained 94.1% of the initial capacitance after 500 bending cycles, manifesting excellent mechanical performance. The study paves a feasible way of facilely constructing temperature regulation mechanism based on MPCMs for flexible high-performance supercapacitors. Graphical abstract: Image 1 Highlights: Phase change microcapsules were successfully incorporated into the electrode. The in-situ thermal regulation of flexible supercapacitors was realized. The modification of MPCMs effectively suppressed the temperature fluctuation. The proposed temperature regulation mechanism is extremely facile and promising.